Anxiety and Social Support as Predictors of Student Academic Motivation During the COVID-19 - Camacho, Ana; Correia, Nadine; Zaccoletti, Sonia; Daniel, João R. (Frontiers in Psychology, 2021)
In this study we examined whether parents’ perceptions of students’ anxiety as well as perceived support from both teachers and classmates were predictive of changes in students’ academic motivation during the first wave of COVID-19. To this end, we used a retrospective pretest-posttest design together with a latent change score model to analyze our data. From April to May of 2020, 394 Portuguese parents of students in grades 1-9 participated in this study. Our results showed that students’ anxiety and teachers’ social support, as perceived by parents, were highly significant predictors of academic motivation changes. Specifically, we found a negative effect of anxiety and a positive effect of teachers’ social support on students’ academic motivation. Our results did not show, however, a significant predictive role of classmates’ social support. This study provides an important contribution to further understand the intrapersonal and interpersonal factors that are associated with the decline of students’ academic motivation during the COVID-19 pandemic. The pivotal role of teachers in sustaining students’ academic motivation and other relevant educational implications for the ongoing pandemic are discussed.